Effect of Vaginal Cone on Pelvic Floor Muscle Strength in Post- Menopausal Women With Stress Incontinence- Community Based Study: Effect of Vaginal Cone on Pelvic Floor Muscle Strength - Parmar, Lata D.; Patel, Bhavi B. (National Journal of Integrated Research in Medicine, 2018)
Context: SUI is defined as involuntary loss of urine during coughing, sneezing or physical exertion. This is common complaint in post menopausal women. Conservative physical treatments preferred as first choice. This study assessed the effect of vaginal cone on pelvic floor muscle strength in these women. Method: Total 32 subjects recruited. Participants randomly assigned to 2 groups. Control group-1(PFMT) and experimental group-2 (PFMT. + vaginal cone). Group-1, N=15 and group -2, N=17, treatment for 6 weeks was given. Result: Independent T-test between Group-I and Group-II showed both groups were homogenous. Paired T-test to compare pre – post difference of variables within the group was significant with p-value <0.01 for Brink score, water glasses per day, frequency of urine per day, leakage episodes. In group 2 majority women with vaginal cone for strength gain reached to 40gms (2-3 subjects progressed to 55gms cone). To check association between 2 variables between groups, chi-square test showed no significant difference, throughout the results significant level was set at 5%. Conclusion: Pelvic floor muscles’ training is effective to improve SUI symptoms and improve quality of life, but effects of vaginal cones need to be studied on larger sample. [Lata P NJIRM 2017; 8(4):10-16]